Ambivalence and Coping Responses in Post-Adoptive Information Systems Use. Issue 3 (2nd July 2020) - Qahri-Saremi, Hamed; Turel, Ofir
ABSTRACT: As information systems (IS) have evolved, more sophisticated meshing of their positive and negative implications has emerged, leaving users with an increasingly ambivalent experience. Given the discomfort of ambivalence, users intrinsically engage in coping responses with different degrees of cognitive flexibility. This paper investigates ambivalence and the coping responses users adopt in the context of post-adoptive IS use via two research questions: (1) what are the consequences of flexible and inflexible coping responses to ambivalence toward post-adoptive IS use? and (2) how does personality influence a user's disposition toward flexible and inflexible coping responses to ambivalence toward post-adoptive IS use? To address them, we propose and test a research model using a multimethod design, comprising two complementary empirical studies. Study 1 adopts a variable-centered approach to test the hypotheses and to empirically validate the proposed research model. Building on the findings of Study 1, Study 2 employs a person-centered approach to identify a typology of IS users. The findings demonstrate the prevalence of ambivalence among IS users, the dual-nature of their coping responses to ambivalence, in part, influenced by their level of neuroticism, and the associated post-adoptive IS use behaviors. This paper provides a novel perspective to users' attitudes toward an IS use and resolves some of the tensions in prior ambivalence research.